Fragmentation techniques for ideal performance in distributed database - a survey - Sharifah Hafizah, Syed Ahmad Ubaidillah; Noraziah, Ahmad; Odili, Julius Beneoluchi (Penerbit UMP, 2020)
Distributed processing is an operative way to improve the performance of the distributed database systems and thus showing the effectiveness of computational intelligence. A specific arrangement of distributed processing through distributed database, where a logically integrated database is physically scattered over several distinct but linked through the computing facilities. Hence, proper fragmentation of data across numerous sites of the network is considered as a significant exploration area in the distributed database environment. Data can be allocated in distinct servers by fragmenting the complete or partially database into several pieces with different techniques. Each piece is stored at the different sites. In this paper, an exploration of fragmentation techniques in distributed database is done. Fragmentation techniques had been proved by many researches in improving the performance of the distributed database system, increase the data accessibility, reduce the transfer cost and access time. This paper presents a survey of numerous fragmentation techniques on distributed database systems.